( x + 1 1 3 x − x 2 ) ( x + x + 1 1 3 − x ) = 4 2
If the roots of the equation above are a , b , c , and d , find 2 0 2 0 ( a + b + c + d ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Chew-Seong Cheong Yes, I think this is the most straightforward solution. :)
RHS is not 4 its 42
Simplifying the given equation we can write x 4 − 1 3 x 3 + 1 7 x 2 − 1 6 1 x + 4 = 0 . Sum of the roots of the equation is 1 3 . So the required answer is 2 0 2 0 × 1 3 = 2 6 2 6 0
Let y=13-x/x+1
So xy(x+y)=42.
But xy+(x+y)=13.
Solving for xy and x+y, we get
X+y=6 and xy=7.
Hence, x=1,6,3+√2,3-√2 giving sum of roots=13
Did you mean to have the equation set equal to 4 2 ? The problem says 4 , but you used 4 2 in your solution and that would make your four roots correct.
The odd thing is, this typo changes the value of the four roots, but not their sum. So people are still getting the problem right.
Problem Loading...
Note Loading...
Set Loading...
( x + 1 1 3 x − x 2 ) ( x + x + 1 1 3 − x ) ( x + 1 1 3 x − x 2 ) ( x + 1 x ( x + 1 ) + 1 3 − x ) ( 1 3 x − x 2 ) ( x 2 + 1 3 ) 1 6 9 x − 1 3 x 2 + 1 3 x 3 − x 4 ⟹ x 4 − 1 3 x 3 + 1 7 x 2 − 1 6 1 x + 4 = 4 = 4 = 4 ( x + 1 ) 2 = 4 x 2 + 8 x + 4 = 0
By Vieta's formula , the sum of roots a + b + c + d = − ( − 1 3 ) = 1 3 ⟹ 2 0 2 0 ( a + b + c + d ) = 2 6 2 6 0 .